2021
DOI: 10.21037/atm-21-1883
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of poly (ADP-ribose) polymerase (PARP) inhibitors in cancer: a network meta-analysis of randomized controlled trials

Abstract: Background: Poly (ADP-ribose) polymerase (PARP) inhibitors, which are among the most important breakthroughs in precision medicine, have played a crucial role in cancer treatment. Understanding the toxicity profiles of the different PARP inhibitors will improve strategic treatment in clinical practice. Methods: PubMed, Cochrane Library, and Web of Science were systematically searched to include related studies published in English between January 2009 and February 2020. Only prospective, phase II and III rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
(90 reference statements)
4
3
0
Order By: Relevance
“…We found that the overall signals for niraparib and rucaparib were stronger than those for olaparib, including symptoms of nausea, vomiting, diarrhea, and constipation, but olaparib had a strong signal in the ileus at the PT level. This was consistent with several systematic reviews (Bao et al, 2021). Gastrointestinal toxicity is one of the most frequent AEs associated with PARPis, often occurring early after treatment initiation.…”
Section: Gastrointestinal Disorderssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the overall signals for niraparib and rucaparib were stronger than those for olaparib, including symptoms of nausea, vomiting, diarrhea, and constipation, but olaparib had a strong signal in the ileus at the PT level. This was consistent with several systematic reviews (Bao et al, 2021). Gastrointestinal toxicity is one of the most frequent AEs associated with PARPis, often occurring early after treatment initiation.…”
Section: Gastrointestinal Disorderssupporting
confidence: 92%
“…In pivotal PARPi RCTs, the most common AEs that have led to dose modifications were hematologic toxicities; other common AEs associated with this class of therapy include gastrointestinal disorders, photosensitivity, and fatigue (Mirza et al, 2016;Pujade-Lauraine et al, 2017). A recent metaanalysis showed that niraparib and rucaparib had higher risks for hematological and gastrointestinal toxicities, and olaparib has a higher risk of serious adverse events (SAEs), such as myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) (Bao et al, 2021;Morice et al, 2021). Unfortunately, there is little knowledge about differences between PARPis.…”
Section: Introductionmentioning
confidence: 99%
“…Hematologic toxicities are a common class effect of PARPi, often occurring early after treatment initiation; they are also the most common cause of dose modification, interruption, and discontinuation [ 4 ]. In our study, rates of hematologic CEIs were consistent with RCT data [ 7 , 8 ] and were higher with niraparib, followed by rucaparib and then olaparib. Differences between PARPi in terms of tolerability and dose modifications in pivotal RCTs in the OC maintenance setting have recently been highlighted in an indirect treatment comparison [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…Differences between PARPi in terms of tolerability and dose modifications in pivotal RCTs in the OC maintenance setting have recently been highlighted in an indirect treatment comparison [ 18 ]. Specifically, any grade 3–4 AEs were observed less frequently with olaparib than with niraparib and rucaparib [ 18 ], which is consistent with the results of a recent network meta-analysis of RCTs [ 7 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation